2001
DOI: 10.4088/pcc.v03n0401
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic-Pituitary-Adrenal Axis in Major Depressive Disorder

Abstract: BACKGROUND: One of the most enduring and replicated findings in biological psychiatry is activation of the hypothalamic-pituitary-adrenal (HPA) axis in a subset of patients with major depressive disorder. This review will discuss some of these findings and their pertinence to the assessment and treatment of depressed patients. METHOD: MEDLINE, PsychINFO, and Current Contents databases were searched for pertinent articles on the HPA axis in patients with depression. In addition, hand searches were conducted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(125 citation statements)
references
References 69 publications
3
119
0
3
Order By: Relevance
“…The resulting neuroinflammation increases oxidative stress, which changes neuronal membrane stability and affects catecholamine neurotransmission, a mechanism involved in traditional depressive pathophysiology 35. Similarly, peripheral SA levels increase brain inflammation through activation of toll‐like receptor 4 in the hypothalamus 36 and may be responsible for dysregulation of the hypothalamus‐pituitary‐adrenal axis, a frequent observation in depressed populations 37. Taken together, we postulate that the association of lignoceric acid, PA, and SA with inflammation may be relevant in the progression of depression in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting neuroinflammation increases oxidative stress, which changes neuronal membrane stability and affects catecholamine neurotransmission, a mechanism involved in traditional depressive pathophysiology 35. Similarly, peripheral SA levels increase brain inflammation through activation of toll‐like receptor 4 in the hypothalamus 36 and may be responsible for dysregulation of the hypothalamus‐pituitary‐adrenal axis, a frequent observation in depressed populations 37. Taken together, we postulate that the association of lignoceric acid, PA, and SA with inflammation may be relevant in the progression of depression in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effects of chronic boredom could be further examined with respect to depression. One of the most highly replicated findings in biological psychiatry is the association of prolonged hypersecretion of HPA axis hormones, including cortisol, and depression (Nemeroff & Evans, 1984;Sachar et al, 1985;Varghese & states.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the psychophysiology of boredom in such a manner could also help clarify whether boredom is characterized by an increase or a decrease in physiological arousal. Research has indicated that resting heart rates are elevated in individuals with depression as are cortisol levels (Kamphuis et al, 2007;Nemeroff & Evans, 1984;Sachar et al, 1985;Taylor, 2010;Varghese & Brown, 2001;Whooley et al, 2008). It seems then that both boredom and symptoms of depression may be associated with increased physiological arousal.…”
Section: Boredom and Depressionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is one of the most common psychiatric illnesses with a lifetime prevalence of greater than 17% in the general population (Osterlund et al, 1998;Varghese and Brown, 2001). Several studies have consistently reported that MDD episodes are twice as common in women as compared to men (Angold and Worthman, 1993;Weissman et al, 1993;Kornstein, 1997;Llewellyn et al, 1997).…”
Section: Stress and Anxiety-related Behaviorsmentioning
confidence: 99%